Soil metagenomics reveals the effect of nitrogen on soil microbial communities and nitrogen-cycle functional genes in the rhizosphere of Panax ginseng - Li, Kexin; Lin, Hongmei; Han, Mei; Yang, Limin (Frontiers in Plant Science, 2024)
Nitrogen (N) is the primary essential nutrient for ginseng growth, and a reasonable nitrogen application strategy is vital for maintaining the stability of soil microbial functional communities. However, how microbial-mediated functional genes involved in nitrogen cycling in the ginseng rhizosphere respond to nitrogen addition is largely unknown. In this study, metagenomic technology was used to study the effects of different nitrogen additions (N0: 0, N1: 20, N2: 40 N g/m 2 ) on the microbial community and functional nitrogen cycling genes in the rhizosphere soil of ginseng, and soil properties related to the observed changes were evaluated. The results showed that N1 significantly increased the soil nutrient content compared to N0, and the N1 ginseng yield was the highest (29.90% and 38.05% higher than than of N0 and N2, respectively). N2 significantly decreased the soil NO3 --N content (17.18 mg/kg lower than N0) and pH. This resulted in a decrease in the diversity of soil microorganisms, a decrease in beneficial bacteria, an increase in the number of pathogenic microorganisms, and an significant increase in the total abundance of denitrification, assimilatory nitrogen reduction, and dissimilatory nitrogen reduction genes, as well as the abundance of nxrA and napA genes (17.70% and 65.25% higher than N0, respectively), which are functional genes involved in nitrification that promote the soil nitrogen cycling process, and reduce the yield of ginseng. The results of the correlation analysis showed that pH was correlated with changes in the soil microbial community, and the contents of soil total nitrogen (TN), ammonium nitrogen (NH4 + -N), and alkalinehydrolyzed nitrogen (AHN) were the main driving factors affecting the changes in nitrogen cycling functional genes in the rhizosphere soil of ginseng. In summary, nitrogen addition affects ginseng yield through changes in soil chemistry, nitrogen cycling processes, and functional microorganisms.